Numerical modelling of wellbore behaviour in fractured rock masses - Zhang, Xing; Last, Nigel; Powrie, William; Harkness, Richard (Journal of petroleum science & engineering, 1999)
Wellbore instability problems have been encountered in many gas and oil fields. Fractures and a high differential stress (i.e., a large difference between the principal effective stresses in the horizontal plane) are considered to be major causes of wellbore instabilities, including hole enlargement and high volume caving. This paper describes the results of a series of numerical analyses carried out using UDEC (Universal Distinct Element Code) to obtain a better understanding of wellbore instability. The effects of two different fracture patterns (randomly polygonal fractures and aligned fracture sets) and three different far-field stress conditions have been investigated for various wellbore pressures, corresponding to different mud densities during drilling. It is known that the differential stress has an important influence on wellbore instability. A comparison of the numerical results with the analytical solution for homogeneous elastic behaviour has been carried out. The numerical analysis shows that the effect of a high differential stress is exacerbated by the presence of adversely connected fractures near the bore wall. The drilling mud density significantly affects the deformation of and the mud loss from a wellbore during drilling. It should be chosen carefully in the light of the fracture geometry and far-field stress.